Perceptions of French Costa Ricans professors on emergency remote education in 2020 at the University of Costa Rica - Chao Chao, Kuok-Wa (2021)
During the first cycle of 2020, the professors of the University of Costa Rica adapted, in a few days, their face-to-face courses to the virtual modality in a context of health emergency. Taking this context into account, qualitative exploratory research was proposed requesting a group of French professors (N=19) to respond to an online questionnaire in July 2020. The objective that motivated this research was to analyze teachers' perceptions of virtuality (advantages and difficulties). The perceptions found belong first of all to the socio-affective level, followed by perceptions of pedagogical, logistical and technological difficulties. As for the advantages, they all focus on studying and above all on the development of their autonomy and self-management of learning. Teachers opt for a teaching model in which there are face-to-face courses, hybrids (presence - online courses) and virtual courses instead of a total virtuality of French courses. It is concluded that this type of teaching imposed at the beginning of the pandemic entails major changes in current models and involves greater training of teaching staff to adapt and adapt their courses.